Feeding sorghum stover to Ethiopian goats and sheep: Effect of amount offered on intake, selection and performance - Aboud, A.A.O.; Owen, E.; Reed, J.D.; Said, A.N.; McAllan, A.B. (British Society of Animal Production, 1993)
Compares the response of goats and sheep when offered increasing ad lib quantities of sorghum stover. Examines growth rate, stover offered, stover refused and stover intake vs amount offered.